If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-(1)=26
We move all terms to the left:
5x-(1)-(26)=0
We add all the numbers together, and all the variables
5x-27=0
We move all terms containing x to the left, all other terms to the right
5x=27
x=27/5
x=5+2/5
| 84=j/5-94 | | (7+8)+9=x | | 2(x+6)-12=(x-6)+12 | | 5x-(-15)=26 | | 2w+18=9(w-5) | | -2(-6x-3)=12x-6 | | 8(x-3)+11=35 | | 3m=180° | | -2(-6x-3)=-6 | | 16q+55=599 | | m/12-5=6 | | 0=2+24.5t−4.9t^2 | | 1/2(x-1)=1/3(2x-1) | | 0=2+24.5t−4.9t2 | | g/3-6=1 | | -333=v/13+310 | | m2=40 | | 7q-3(3q+6)=7(6+q) | | x*x=1/81 | | 6(c-79)=84 | | b/10+59=63 | | 4f-29=43 | | 8(x+3)=10x+6 | | 6(y+5)=4y+42 | | 21-3t=18 | | 7r+2=86 | | x/3+9=22 | | 56=t/6+49 | | x=-0.9x^2+2.8x+2.4 | | x=8+2/3 | | 2/3+2x=1/3-3x | | 9=m+24/4 |